FEATURES OF SPATIAL MOBILITY OF THE POPULATION IN THE CONTEXT OF SOCIO-ECONOMIC DEVELOPMENT OF THE ARCTIC ZONE OF YAKUTIA: HISTORICAL CONSEQUENCES AND THE PRESENT STATE - Tomaska; Alyona Georgievna; Sannikova; Yana Mikhailovna (Bulletin Social-Economic and Humanitarian Research, 2022)
In a joint article, in the context of an overview analysis of the population dynamics, migration processes of the population and the historical consequences of the socio-economic development of the Arctic zone of the Republic of Sakha (Yakutia), preliminary results of a study of the spatial mobility of the population, which is being turned into a social resource of society, are presented. At the same time, attention is drawn to the current situation of the indigenous population of Arctic Yakutia, employed in traditional sectors of the economy, including the indigenous peoples of the North.